THE RELEVANCE OF MRS. RUSWO’S STRUGGLE VALUES IN CONTEXTUAL HISTORY LEARNING - Merci Robbi Kurniawanti (CV. Fahr Publishing, 2026)
History learning is not only focused on mastering facts and event chronologies; it also serves as a medium for internalizing the values of struggle to shape students' character and historical awareness. One learning resource with the potential to support this objective is the history of the struggles of local figures-such as Mrs. Ruswo, a female freedom fighter from Yogyakarta who played a pivotal role in defending Indonesia's independence. This study aims to analyze Ibu Ruswo’s values of struggle based on Joyomartono’s framework and to contextualize them within history leaarning. The study use a qualitative method with a historical approach. Data were gathered from prior research on Ibu Ruswo’s struggle, supplemented by primary and secondary sources as well as relevant literature. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing, classifying the data according to Joyomartono’s five values of struggle: willingness to sacrifice, unity, cooperation, patience and perseverance, and mutual respect. The findings indicate that these five values are reflected in mr. Ruswo’s actions during the Dutch East Indies era, the Japanese occupation, and the War of Independence-manifested. These values are highly relevant to history learning, as they can be integrated as local history-based learning resources. This study affirms that contextualizing Ibu Ruswo’s values of struggle offers an alternative approach to developing history education that is more contextual, meaningful, and character-oriented.